Управління та реалізація проєктів, які фінансуються з фондів ЄС, в установах соціальної сфери (на прикладі центрів соціальної допомоги Республіки Польщі) : кваліфікаційна робота на здобуття освітнього ступеня магістр за спеціальністю „8.232.00.01 — Управління установами соціальної сфери“. - Шестакова, К.Ю. (Національний університет "Львівська політехніка", 2023)
Project management is an important component of the functioning of social institutions all over the world, primarily in EU countries. The analysis of scientific and practical sources (Ackah, 2019; Sorychta-Wojsczyk & Musiol-Urbanczyk, 2016; Szymborska et al, 2021) allows us to conclude that the implementation of social projects by institutions of the social sphere acquires great importance in the period of socio-economic transformation. The purpose of the master's research is to analyse the process of development, implementation, and management of social projects (which are financed from the funds of the European Union) in social assistance centres of the Republic of Poland. The object of the research is social assistance centres as subjects of project activity. The subject of the research is the management of projects financed from EU funds in social assistance centres in Poland. In the first chapter of the master's research, it is proposed to consider design as a socio-scientific activity and value. The second section is devoted to the analysis of the work of social assistance institutions from the point of view of institutions of the social sphere, because they act as subjects of project activities, primarily within the framework of financing by the EU. In the third chapter, the conclusion is substantiated that with the accession to the EU, projecting as a method of transforming the surrounding reality has gained special importance in the public administration of Poland. Conclusions. Analysis of the projects implemented by individual social assistance centres in Poland shows that the purpose and content of the projects are in most cases complementary to strategic documents for the development of settlements or communities. The analysis of specific examples of the work of social assistance centres and family support centres in individual voivodships proved that there are a few external and internal factors that affect the success of the project and management decisions at various stages of project implementation. Among the most important points to pay attention to may be the following. First, project management is impossible without the creation of a team and consulting support at various stages of the project (from application to summarizing). Secondly, the process of involving potential participants in project transformations takes on an extremely important role. It is about the motivation and interest of the residents of the community to whom the project is addressed. Thirdly, the situation on the local labour market should be considered in the process of planning project activities.
Keywords: Social project, social assistance centre, project management, European structural funds, Poland, European Union, social protection institutions